PENERAPAN METODE KARYAWISATA TERHADAP KEMAMPUAN BERBAHASA EKSPRESIF (BERBICARA) ANAK USIA 5-6 TAHUN DI TK DARUL FALAH PONPES SAMARINDA TAHUN PEMBELAJARAN 2017/2018 - Farny Sutriany Jafar; Fitriyani - Arifin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
The research was intended to know how teacher devise learning of study tours method, to know expressive language skills (speaking) of children with applied method of study tours and to know supporting and inhibitor factors in its application. The research was dome in Darul Falah Ponpes Kindergarten Samarinda on 5-6 years old children in B2 class, with total of student was 13. The research was qualitative research, descriptive with case study approaching. In this research data was acquired using data collecting technic that was observation, interview and documentation. The result shown that (1) teacher devised learning with karyawisata method was establishing program of study tours learning, set the date and destination, permission request, planning implementation of study tours, giving the information to parents of students, preparation of teacher in the class, preparing of tools and material, funding, dividing preceptor group, assign the rules, praying, and explain students about the purpose that need to acquire from karyawisata; (2) expressive language skills (speaking) of children in B2 class with indicators was asking, answering, and retelling, achieving the result of growing as expected (BSH) ; (3) supporting factors was enthusiastic and student’s activeness, good teamwork between foundation, preceptors, parents, and owner of study tours spot, recalling activity in every study tours activity, and teacher’s activeness in giving referrals. While inhibitor factors are unpredictable weather, high cost, not all study tours spot has guide, limitation of time in study tours spot, and lack of exemplary in good language using when giving referrals.